Leiomyosarcoma of the abdomen and retroperitoneum; a systematic review - Øines, Mari Nanna; Smith, Henry George; Preisler, Louise; Penninga, Luit (Frontiers in Surgery, 2024)
Abstract Leiomyosarcoma of the abdomen and retroperitoneum; a systematic review. Background Intraabdominal and retroperitoneal leiomyosarcomas are rare cancers, which cause significant morbidity and mortality. Symptoms, treatment and follow up differs from other cancers, and proper diagnosis and treatment of intraabdominal and retroperitoneal leiomyosarcomas is of utmost importance. We performed a systematic review to collect and summarize available evidence for diagnosis and treatment for these tumours Methods We performed a systematic literature search of Pubmed from the earliest entry possible, until January 2021. Our search phrase was (((((colon) OR (rectum)) OR (intestine)) OR (abdomen)) OR (retroperitoneum)) AND (leiomyosarcoma). All hits were evaluated by two of the authors. Results Our predefined search identified 1983 hits, we selected 218 hits and retrieved full-text copies of these. 144 studies were included in the review. Discussion This review summarizes the current knowledge and evidence on non-uterine abdominal and retroperitoneal leiomyosarcomas. The review has revealed a lack of high-quality evidence, and randomized clinical trials. There is a great need for more substantial and high-quality research in the area of leiomyosarcomas of the abdomen and retroperitoneum.